Close together or far apart? The geography of host-country knowledge sourcing and MNCs' innovation performance. Issue 2 (1st February 2023) - Perri, Alessandra; Santangelo, Grazia D.
ABSTRACT: We investigate the influence of different host-country knowledge sources on the quality and generality of multinational corporation (MNC) innovation. We suggest that the quality of MNC innovation increases with the geographical distance from local industrial organizations. We also argue that the generality of MNC innovation increases with the distance from local research institutions, but decreases after a certain threshold. We explain these relationships based on the different cognitive and geographical distances separating MNC innovation activities from industrial organizations and research institutions. We test our arguments on a sample of US Patent and Trademark Office (USPTO) patents developed in the United States by foreign semiconductor MNCs.